2020
DOI: 10.1590/0004-282x20190143
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of headache after reduction of prolactin levels in hyperprolactinemic patients

Abstract: Prolactin (PRL) secreting adenomas are associated with high incidence of headache. The role of hyperprolactinemia in the headache context is not clear, nor is the effect of its treatment on headache. Methods: The present longitudinal study evaluated hyperprolactinemic patients (69), in terms of presence and characteristics of headache before and after hyperprolactinemia treatment. Results: Headache was reported by 45 (65.2%) patients, independent of the etiology of hyperprolactinemia. The migraine phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Therefore, D2 receptor antagonists are recommended on the treatment of acute migraine attacks (67,68). D2 receptor agonists, however, relieve migraine pain in the presence of prolactinoma (56,69). Further studies with control groups investigating the correlation of pain relief and PRL level are needed to draw a conclusion on PRL involvement in treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, D2 receptor antagonists are recommended on the treatment of acute migraine attacks (67,68). D2 receptor agonists, however, relieve migraine pain in the presence of prolactinoma (56,69). Further studies with control groups investigating the correlation of pain relief and PRL level are needed to draw a conclusion on PRL involvement in treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Enhances PRL secretion in rodents [78]. patients with prolactinomas compared to nonfunctioning pituitary adenomas (54) and lowering PRL levels with D2 receptor agonist relieved headache in hyperprolactinemic patients (56).…”
Section: Adenosinementioning
confidence: 99%
See 1 more Smart Citation
“…Usually, prolactinoma-associated headaches are localized on the same side as the tumor and respond well to dopamine agonists [ 9 , 53 ]. A longitudinal study [ 10 ] evaluated patients with hyperprolactinemia for presenting the characteristic of headache before and after treatment by D 2 agonists. In this study, prolactin levels were decreased after treatment and the pain subsided.…”
Section: Prolactin and Migraine: Clinical Researchmentioning
confidence: 99%
“…Historically, two lines of evidence have been presented that link prolactin and migraine. First, in hyperprolactinemia, headaches with migraine characteristics have been described and normalization of the prolactin level has alleviated headaches [ 9 , 10 ]. Moreover, in migraine patients, higher levels of prolactin have been identified that were also responsive to drugs lowering the prolactin level [ 11 , 12 ].…”
mentioning
confidence: 99%